2022
DOI: 10.1186/s12864-021-08248-z
|View full text |Cite|
|
Sign up to set email alerts
|

RAD gene family analysis in cotton provides some key genes for flowering and stress tolerance in upland cotton G. hirsutum

Abstract: Background RADIALIS (RAD), belongs to the MYB gene family and regulates a variety of functions including floral dorsoventral asymmetry in Antirrhinum majus and development of fruit proteins in Solanum lycopersicum. RAD genes contain an SNF2_N superfamily domain. Here, we comprehensively identified 68 RAD genes from six different species including Arabidopsis and five species of cotton. Results Phylogenetic analysis classified RAD genes into five gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 114 publications
0
9
0
Order By: Relevance
“…The miR3457 is known to regulate the WSC domain–containing protein having a function in cell wall formation ( Tarver et al, 2015 ), whereas miR7743 was found associated with dormancy release ( Zhang et al, 2018 ). miR1440 was identified which functions by targeting the RAD (RADIALIS) gene of the MYB gene family and thereby regulates cell proliferation and cell cycles ( Kabir et al, 2022 ). In addition, many developmental pathways are found regulated by miR902 and miR7511 ( Berruezo et al, 2017 ; Zhang et al, 2019 ) and miR5543, having a role in cell transport ( Achakzai et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The miR3457 is known to regulate the WSC domain–containing protein having a function in cell wall formation ( Tarver et al, 2015 ), whereas miR7743 was found associated with dormancy release ( Zhang et al, 2018 ). miR1440 was identified which functions by targeting the RAD (RADIALIS) gene of the MYB gene family and thereby regulates cell proliferation and cell cycles ( Kabir et al, 2022 ). In addition, many developmental pathways are found regulated by miR902 and miR7511 ( Berruezo et al, 2017 ; Zhang et al, 2019 ) and miR5543, having a role in cell transport ( Achakzai et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In response to environmental stresses, stress-responsive CAEs enhance plant resistance through the activation of various stressrelated genes. 44 In the promoter region of FvMES genes, several CAEs, including STRE, ARE, MYB (MYB, MYB-like, and MBS), and WRKY (W-box), have been identified. Previous literatures had shown that these CAEs are responsive to abiotic stresses, including drought, gibberellic acid (GA), and abscisic acid (ABA) in various plant species.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudogenes emerge from neutral selection when the Ka/Ks ratio is 1, purifying selection favors duplicated genes with a Ka/Ks ratio below 1, and positive selection of rapid evolution is shown with a Ka/Ks ratio above 1. All the COBLs have Ka/Ks ratios below 1, suggesting that the COBL gene family was subject to purifying selection over the course of evolution ( Niu et al., 2015 ; Bano et al., 2021 ; Kabir et al., 2022 ). The Ka/Ks ratios for PtrCOBL12-PtrCOBL3 and PtrCOBL8-PtrCOBL10 were the lowest among the paralogous genes, indicating these genes were able to keep their original roles despite their shorter divergence dates.…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression control occurs primarily via transcriptional regulation, which requires interaction between transcription factors and promoter binding sites ( Wang et al., 2022 ). Specific and consistent cis-acting elements in promoter regions are required for different external signals to activate inducible promoters; for example, auxin-induced promoters typically contain cis-acting elements of the AuxRE, and light-induced promoters typically contain cis-acting elements rich in the AT-rich motif, the I-box, the G-box, and the GT1-motif ( Kabir et al., 2022 ; Wang et al., 2022 ). Similarly, drought-induced promoters included the cis-acting elements CACG and CATGTG.…”
Section: Discussionmentioning
confidence: 99%